Evaluasi Pelaksanaan Kurikulum Merdeka Di Sekolah Dasar: Tinjauan Dampaknya Terhadap Prestasi Belajar Siswa - Ulya Ainur; Samporno (Tadzkirah : Jurnal Pendidikan Dasar, 2023)
Curriculum evaluation is a series of activities to assess whether there is a gap between the theoretical concept of the curriculum and the reality in the field so that this influences or impacts student learning achievement. This research focuses on the impact that the independent curriculum has on student learning achievement, so that the independent curriculum needs to be evaluated or reviewed. This research uses a qualitative descriptive method with literacy study data collection techniques. The results of this research are that there is a need to evaluate the independent learning curriculum because the impact of implementing this independent curriculum is a negative impact on student learning achievement in elementary or elementary schools.